(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Historical terms have a tendency to be “mobile” in terms of geographical space and historical time. The presentation of historical terms by means of a mobile dictionary enabling university students to access such terms by means of a smartphone, tablet or laptop adds to the dimension of mobility. The article describes the continuous change in meaning of historical concepts over time and space with reference to democracy and nationalism, which are known as substantive concepts. An analysis of the emergence and development of these concepts within different historical contexts indicates the extent to which static definitions are inadequate with regard to fostering historical understanding. A tendency to continuous change in the meaning of the above-mentioned terms has important implications for the compilation of a Language for Specific Purposes (LSP) dictionary of historical terms at university level, and for the consequences thereof for mobile LSP lexicography. The LSP dictionary called MobiLex has a pedagogical purpose and changes in the design and features of the dictionary to enhance teaching and learning of historical terms have pedagogical consequences regarding the learning of such terms. In an ever-changing environment, adaptions to mobile lexicography would be possible with the advancement of technology. Trends and development in technology offer the possibility of changing the face of lexicographical support in a mobile environment, motivated from a pedagogical theoretical point of view.